Methodological Bases of Formation of Chemical Concepts in Pupils in School from Chemistry Course - E.Shamurodov; Sh.Sharipov; G’.Sharifov; X.Juraev; J.Bazorova (Zien Journals, 2022)
Human rights are inextricably linked. In the African charter, collective rights and individual rights are interdependent and indivisible. it is difficult to protect individual rights if collective rights are not guarantee. The rights of minorities are guarantee by United Nations charter and its relevance to the republic of Cameroon where the anglophone minority since independence continuously has complained of marginalization. These complaints have been to the effect that severe violations of the human right of anglophone Cameroonians have occurred. This article seeks to however, established the legislations put in place by the government to protect the rights of these minority English speaking regions.
Keywords: Legal Framework; protection; English speaking; minority